FMEA and PMBOK applied to project risk management (Journal of Information Systems and Technology Management, 2008)
This paper presents a risk management tool based on two well-known sets of concepts: FMEA (Failure Mode and Effect Analysis) and PMBOK (Project Management Body of Knowledge). After presenting an adherence analysis between the suggested model and PMBOK, we apply the proposed instrument in a real case study: an ERP implementation at the largest Brazilian mail service and logistics organization. The main results show that the proposed model was largely successful because it identified and classified risks. Furthermore, the model helped to document the strategies and action plans needed to respond to these risks.